POTENTIAL OF INQUIRY-BASED LEARNING TO TRAIN STUDENT'S METACOGNITIVE AND SCIENCE PROCESS SKILL - Damopolii, Insar; Keley, Umar; Rianjani, Devi Tutut; Nunaki, Jan Hendriek; Nusantari, Elya; Kandowangko, Novri Youla (Jurnal Ilmiah Peuradeun, 2020)
The learning process in high schools in West Papua tends to focus on students? cognitive enhancement and ignore the aspect skill. School is the frontline to develop students? skills. Metacognitive and process skills are the two skills needed by the students, and both should be trained and developed. These two skills help students to implement an investigation process in which the investigation process can be well utilized using inquiry-based learning. This study aims to find out the differences in metacognitive and process skills between students treated with inquiry-based learning and those who are taught using conventional learning. This experimental study was carried out at Grade X of senior high school students of SMA Negeri 1 Manokwari. The result reveals a significant metacognitive skill of 0.000 < ? 0.05, and science process skill of 0.001 < ? 0.05 of students who were taught using the inquiry-based learning more than those who were taught using the conventional learning. It can be concluded that there is a significant improvement in students? metacognitive and process skills for those who are taught using inquiry-based learning compared to those who are taught using conventional learning. Therefore, inquiry-based learning has the potential to appropriately train students? metacognitive and science process skill.